PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN SISTEM PENGENDALIAN INTERNAL PEMERINTAH TERHADAP KINERJA APARATUR PEMERINTAH (STUDI PADA DINAS PERTANIAN DAN PETERNAKAN KABUPATEN NAGAN RAYA) - PURWATI, Tesa Putri; Marlina, Lilis (Akbis: Media Riset Akuntansi dan Bisnis, 2021)
ABSTRACTThis study aims to determine the influence of participation in budget preparation and internal government control system on the performance of government apparatus of the Department of Agriculture and Livestock Nagan Raya Regency. The population in this study is all employees of the Department of Agriculture and Livestock Nagan Raya Regency. The selection of samples using the census method, and obtained as many as 37 people. The data analysis method used in this study is multiple linear regression analysis using SPSS and Microsoft excel programs. Based on the results of the study, it is known that partially, the participation of budget preparation has no effect on the performance of government apparatus. The internal control system affects the performance of government apparatus. While simultaneously participation in the preparation of budgets and internal control systems have a significant effect on the performance of government apparatus.Keywords: Participation in Budget Preparation, Internal Control System and Performance of Government Apparatus.